Are the asymmetries of the orthostatic posture random? - GAGEY, P.-M.; ASSELAIN, B.; USHIO, N.; LECONTE, M.; BARON, J.B. (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Three posture asymmetries and their connections were assessed by a statistical study as rigorous as possible on the subjects of a sample from a population considered as normal after negative criteria. The comparison of probabilities observed with random probabilities shows that there is less than one chance in a thousand to make an error by rejecting the hypothesis that the asymmetries of the orthostatic posture are random. The definition of the limits of these asymmetries thus fits in the search for the conditions of a clinical examination of the posture.